ISLAM (DI) NUSANTARA; ESENSI, GENEALOGI SERTA IDENTITASNYA ISLAM (IN) ARCHIPELAGO; ITS ESSENCE, GENEALOGY, AND IDENTITY - Syauqi, Muhammad Labib (Universitas Islam Negeri Raden Intan Lampung, 2015)
This paper tries to explain about the details of Islam of Archipelago which is now getting the momentum back, even though the initial idea about Islam of Archipelago is not really new. Islam of Archipelago attempts to make a dialogue from religious text which comes from the revelation with local contents on earth, to actualize limited text of religion with unlimited social phenomenon in society. Islam of Archipelago is on the effort to find the possible various interpretations without changing the law itself. Because the existence of text is limited whereas a social phenomenon is unlimited, even it is dynamically developing, the process of dynamic dialectic proves that Islam is appropriate in any place and everlasting any time.